New threats in the cyberspace based on the analysis of The Onion Router - Nastuła, Anna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2016)
New technologies change the society and generate new threats with respect to hiding human identity on the Internet. The aim of the paper is to present the origins, functioning and actual application of the TOR (The Onion Router) network. The author discusses the issue of anonymity as a driving force behind the TOR network which was ignited by social and political problems on the international arena. Also the relevance of TOR for the free flow of information and freedom of social communication on the Internet as well as thematic cross-section of its resources are presented. Further on in the paper the author shows a payment system in the TOR network which is based on cryptocurrencies, mainly on Bitcoin, and proves to be an ideal means of payment for illegal transactions. The paper also lists the most frequently committed crimes now and warns that the newly emerging forms of crimes which rely on anonymizing technologies, will pose a real challenge for law enforcement agencies and the system of justice. The TOR network by providing criminals with anonymity speeds up the development of cyber crime on an unprecedented scale and transfers traditional crime into a completely new dimension. The TOR network may have been well-meaning originally but has become a global threat.